Real Exchange Rates and Competitiveness : A Clarification of Concepts, and Some Measurements for Europe - Lipschitz, Leslie (IMF Working Papers; Working Paper, 1991)
This paper examines indicators of competitiveness. It analyzes the conceptual foundations of conventional measures of the real exchange rate and finds that inferences about competitiveness from these indicators require strong, and in many cases implausible, assumptions. Based on this analysis some alternative measures are proposed and their use is illustrated using data from Europe. Given the usefulness of standardized indicators, four simple charts are proposed; these help solve some conundrums in the European data and provide the basis for a richer set of inferences about competitiveness.